To be or not to be? That is the question - Romero Cevallos, Marco (2016)
This article analyzes the main elements of the current state of the Andean Community and the prospects for its integration process. It centers on the stance of the members of the community toward the FTAA and toward bilateral trade agreements with the United States. The article concludes with an exploration of how the new orientation proposed for the community by its General Secretariat might change the community's positions.